Multisensory experiences in virtual environments: The role of sense of power, cognitive flexibility and personality traits - Guerreiro, J.; Loureiro, S. M. C.; Bilro, R. G.; Villar, J. (Proceedings of the 49th European Marketing Academy Conference (EMAC), 2020)
The technological advances such as Virtual Reality are creating opportunities for business. However, there is a lack of studies that consider tactile, smell and taste senses found in literature. Thus the aims of this study are: (i) explore how cognitive flexibility influences sense of power and consequently the intention to return in a context of a virtual reality coffee shop; (ii) analyze the moderating effect of the different sensory experiences in the relationship between sense of power and the intention to return (iii) analyze personality traits as moderator of cognitive flexibility and sense of power. Results show that cognitive flexibility positively explains sense of power and personality traits moderates the relationship between the two. However, results show that sense of power does not significantly explains return intentions. Furthermore, there is no impact of the insertion of the variable Sensory experience on the relation between sense of power and return intentions.